Online Teaching and Learning Aids: in the Lens of Course Content Development in Faculty of Information Management Universiti Teknologi MARA - Osman, Suhaila; Anuar, Muhammad Asyraf Wahi; Ahmad, Rohayu; Kamarudzzaman, Azura A. Jamil @; Mohamed, Al-Bakri (2017)
The use of technology gives big impact towards the transformation of education itself. Learning Management System (LMS) is now needed to direct the resource allocation and investment decisions concerning to the development and the adoption of new and emerging information technologies due to support the students learning process in the university. This study proposes an online teaching and learning aids as a tool in publishing course content development. The ADDIE model is used as a basic model for content management system in this study. A set of questionnaire was utilised as an instrument to investigate the level of creativity, innovation and skills of students through the learning outcome and to propose a new model in fulfilling the learning outcome requirements. Stratified Random Sampling was used as the sampling design, whereby 213 respondents were chosen among students from four different branches that offer Electronic Publication (IMD214) course under the Faculty of Information Management, that are located in Johor, Kelantan, Kedah and Sarawak. The findings of this study revealed that new mechanism needs to be practised in teaching and learning environment nowadays in order to support the 11th Malaysia Development Plan that consists of three areas namely Dynamic Graduate, High Quality Education and Accessibility. The model, therefore, can be viewed as a map which would guide other universities appropriately in enhancing their LMS for their own education purpose.